Studi Kuantitatif: Pengaruh Kesadaran Konsumen, Kepercayaan Merek, dan Sertifikasi Halal terhadap Minat Beli di Bagus Bakery - Prianda Pebri; Faulia Anggeraini (Institut Nalanda, 2024)
This study was conducted at Bagus Bakery MSMEs to investigate the influence of consumer awareness, brand trust, and halal certification on the purchase interest in Bagus Bakery products. Employing a quantitative research approach grounded in positivism philosophy, data were gathered using a questionnaire distributed via Google Forms to 90 respondents who had purchased Bagus Bakery products in May and resided in Gedangan Village. The data were analyzed using SPSS software. The t-test results indicated that consumer awareness, brand trust, and halal certification each had a significant and positive impact on purchase interest. Furthermore, regression analysis yielded an R² value of 0.836, demonstrating that 83.6% of the variance in purchase interest is explained by these three variables, with the remaining 16.4% attributable to other factors.